COMPUTER TESTING IN THE SYSTEM SUCCESS MONITORING OF FUTURE MASTERS (M(P)HEI) - Kuchyn, Yuriy; Vlasenko, Oleg; Kucherenko, Inna; Mikitenko , Pavlo (Physical and Mathematical Education, 2022)
Formulation of the problem. The article presents the results of scientific research on the functioning of the system of monitoring the success of future masters of medical (pharmaceutical) institutions of higher education (M(P)HEI). One of the elements of the performance monitoring system is the rector’s section of students’ knowledge of disciplines included in the Unified State Qualification Examination. Materials and methods. A set of scientific research methods was used to perform the tasks of the research, namely: bibliosemantic method, method of system analysis, testing of future masters of (M(P)HEI) on the distance learning platform LIKAR_NMU, statistical methods, analysis of statistical data in research groups, determining the reliability of tests (Cronbach’s alpha), the complexity and discrimination index of test tasks. Results. According to the results of online testing, the indicators of the absolute and qualitative success of future masters of (M(P)HEI) were determined. A comprehensive examination of the quality of test tasks after the rector’s section was carried out, allows to improvement of the quality of test materials and forms a bank of standardized test tasks and tests. In particular, the criteria of reliability of tests were determined using the Cronbach’s alpha coefficient, which gave grounds to state the "high" and "very high" reliability of tests. Psychometric analysis of test tasks was performed and diagrams of psychometry of test tasks were constructed to correct test materials. Conclusions. Conducting a quarterly rector’s section provides an opportunity to systematically monitor student performance and adjust their learning trajectory. The introduction of testing in the educational process of (M(P)HEI) is a significant step towards the development of methods of diagnosis and control of the level of acquired knowledge of students. However, testing should not replace traditional methods of pedagogical control and diagnosis, but should only to some extent complement them.